2005
DOI: 10.1038/sj.hdy.6800719
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of genetic diversity among disjunct populations of the rare forest understory herb, Trillium reliquum

Abstract: We assessed genetic diversity and its distribution in the rare southeastern US forest understory species, Trillium reliquum. In all, 21 loci were polymorphic (P S ¼ 95.5%) and the mean number of alleles per polymorphic locus was 3.05. However, genetic diversity was relatively low (H es ¼ 0.120) considering the level of polymorphism observed for this outcrossing species. A relatively high portion of the genetic diversity (29.7%) was distributed among populations. There was no relationship between population siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 42 publications
1
17
0
1
Order By: Relevance
“…At the same time, our data showed that total genetic diversity at species level was higher in widespread R. angustifolius and R. rumelicus compared with the insular endemic R. osiliensis (Table 4). This result is in agreement with many other studies, which found that endemics nearly always had lower levels of genetic diversity compared with common species (Gonzales and Hamrick 2005;Gibson et al 2008;Gonzales-Perez et al 2009;Talve et al 2011). The genetic variation in populations of R. angustifolius varied considerably.…”
Section: Discussionsupporting
confidence: 95%
“…At the same time, our data showed that total genetic diversity at species level was higher in widespread R. angustifolius and R. rumelicus compared with the insular endemic R. osiliensis (Table 4). This result is in agreement with many other studies, which found that endemics nearly always had lower levels of genetic diversity compared with common species (Gonzales and Hamrick 2005;Gibson et al 2008;Gonzales-Perez et al 2009;Talve et al 2011). The genetic variation in populations of R. angustifolius varied considerably.…”
Section: Discussionsupporting
confidence: 95%
“…Most of the studies on effects of habitat fragmentation are dealing with processes that occurred in the last decades or centuries due to human activities (Gonzales and Hamrick, 2005) such as changes in land use (e.g. Jacquemyn et al, 2003;Robinson and Sutherland, 2002;Stoate et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary succession frequently leads to the fragmentation of communities and isolation of populations [5][6][7]. Small and isolated populations may suffer from a low level of genetic diversity and a high risk of individual mortality, frequently resulting in their extinction [8][9][10][11]. On the other hand, Czarnecka and Denisow [12] argued that genetic variability of small populations might be improved by long-distance moving pollinators.…”
Section: Introductionmentioning
confidence: 99%